Sociálnĕ lékarské aspekty stresů a adaptací - Drbal, C (Ceskoslovenske zdravotnictvi, 1990)
Based on a recapitulation of contemporary knowledge on stress and adaptations, the author investigates and analyzes sociomedical aspects of this problem. He draws conclusions on the necessity of some new theoretical views on the relationship of social and biological processes, laws and new approaches to the actual implementation of this relationship in conjunction with health protection and promotion of people in contemporary society.
Keywords: Humans; psychický stres; Adaptation, Psychological; adaptace psychologická; Stress, Psychological; lidé